Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.6 Rational Exponents - R.6 Exercises - Page 64: 83


$\color{blue}{-4k^{10/3} + 24k^{4/3}}$

Work Step by Step

RECALL: (1) $a(b+c) = ab + ac$ (2) $a^m \cdot a^n = a^{m+n}$ Use rule (1) above to obtain: $=-4k \cdot k^{7/3} - (-4k) \cdot 6k^{1/3} \\=-4k \cdot k^{7/3} +4k\cdot 6k^{1/3}$ Use rule (2) above to obtain: $=-4k^{1+(7/3)} + 24k^{1+(1/3)} \\=-4k^{3/3+7/3} + 24k^{3/3+1/3} \\=\color{blue}{-4k^{10/3} + 24k^{4/3}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.